2020
DOI: 10.1002/hep.30887
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Activation in Liver Macrophages Protects Against Hepatic Endoplasmic Reticulum Stress in Mice

Abstract: Background and Aims Hepatic endoplasmic reticulum (ER) stress, whether triggered by intrinsic or extrinsic factors, can be resolved by the unfolded protein response (UPR). Sustained UPR activation leads to cell death and inflammatory response and contributes to liver disease progression. Hepatic tissue macrophages are key players in orchestrating liver inflammation, and ER stress can enhance macrophage activation. However, it is not well defined how the interplay between ER stress and inflammation is regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 44 publications
(96 reference statements)
2
35
1
Order By: Relevance
“…Multiple previous literatures have confirmed that the activation state of VDR can modulate the functions of non-parenchymal and parenchymal liver cells, such as fibrogenesis, integrity of biliary epithelial cells, liver cancer, and BA metabolism. Recently, two studies published in Hepatology further emphasized the importance of VDR in regulating inflammatory response, and VDR activation by VDR ligands may be useful as a potential method for treating multiple liver diseases (Dong et al, 2019;Zhou et al, 2019). In previous studies, vitamin D3 has been proved to abate fibrosis and modulate BA regulatory genes in BDL-induced cholestasis (Ogura et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple previous literatures have confirmed that the activation state of VDR can modulate the functions of non-parenchymal and parenchymal liver cells, such as fibrogenesis, integrity of biliary epithelial cells, liver cancer, and BA metabolism. Recently, two studies published in Hepatology further emphasized the importance of VDR in regulating inflammatory response, and VDR activation by VDR ligands may be useful as a potential method for treating multiple liver diseases (Dong et al, 2019;Zhou et al, 2019). In previous studies, vitamin D3 has been proved to abate fibrosis and modulate BA regulatory genes in BDL-induced cholestasis (Ogura et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β, CRP, TNF-α, and IL-6 are commonly used indicators to assess the risk of cardiovascular events ( 41 , 42 ). These pro-inflammatory cytokines are also closely related to the occurrence and prognosis of NAFLD disease ( 43 , 44 ). Therefore, regulating lipids and inhibiting inflammation have become an important way to combat AS in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data and indirect evidence also show a possible role for vitamin D in reducing complications attributed to and the cytokine storm itself[ 52 ]. Moreover, recent research revealed that vitamin D receptor signaling in macrophages regulates a shift between proinflammatory and anti-inflammatory activation during ER stress-induced inflammation[ 53 ]. Thus, supplementation within recommended upper safety limits, for specific nutrients such as vitamins C and D, warrants optimal nutritional status to insure a well-functioning immune system protecting against viral infections[ 54 ].…”
Section: Discussionmentioning
confidence: 99%